KELTIMINAR CULTURE - H.H. Egamberganov (Journals Park Publishing, 2023)
This article is supposed to highlight the sources and data obtained in the course of new studies of the Keltiminar Neolithic culture. In the course of the work carried out by the staff of the Institute of Archeology of the Academy of Sciences of Ruz, the Uzbek-Polish, Uzbek-French international archaeological expeditions, the monuments of Ayakagitma, Ayakagitma 2, Mount Sultan Uvais, examined the location of individual finds. In addition, the paper highlights the approach to the question of the genesis of the Keltiminar culture in the light of the emergence of new data.
Keywords: Neolithic era, Keltiminar culture, VII-VI millennium BC, S.P. Tolstov, A.V. Vinogradov, lower reaches of the Amudarya, Kyzylkum, Ayakagitma, Ayakagitma 2, Sulton Uvais, genesis.